Blue: Color and Concept. BEINECKE RARE BOOK & MANUSCRIPT LIBRARY, YALE UNIVERSITY - Vega, Carolyn (Archivaria, 2014)
Blue: Color and Concept. BEINECKE RARE BOOK & MANUSCRIPT LIBRARY. Mounted at the Beinecke Library, Yale University, New Haven, Connecticut. 21 January to 19 April 2014. Curated by NANCY KUHL.